Enhanced transgene expression in sugarcane by co-expression of virus-encoded RNA silencing suppressors. - San-Ji Gao (Public Library of Science (PLoS), 2013)
Post-transcriptional gene silencing is commonly observed in polyploid species and often poses a major limitation to plant improvement via biotechnology. Five plant viral suppressors of RNA silencing were evaluated for their ability to counteract gene silencing and enhance the expression of the Enhanced Yellow Fluorescent Protein (EYFP) or the β-glucuronidase (GUS) reporter gene in sugarcane, a major sugar and biomass producing polyploid. Functionality of these suppressors was first verified in Nicotiana benthamiana and onion epidermal cells, and later tested by transient expression in sugarcane young leaf segments and protoplasts. In young leaf segments co-expressing a suppressor, EYFP reached its maximum expression at 48-96 h post-DNA introduction and maintained its peak expression for a longer time compared with that in the absence of a suppressor. Among the five suppressors, Tomato bushy stunt virus-encoded P19 and Barley stripe mosaic virus-encoded γb were the most efficient. Co-expression with P19 and γb enhanced EYFP expression 4.6-fold and 3.6-fold in young leaf segments, and GUS activity 2.3-fold and 2.4-fold in protoplasts compared with those in the absence of a suppressor, respectively. In transgenic sugarcane, co-expression of GUS and P19 suppressor showed the highest accumulation of GUS levels with an average of 2.7-fold more than when GUS was expressed alone, with no detrimental phenotypic effects. The two established transient expression assays, based on young leaf segments and protoplasts, and confirmed by stable transgene expression, offer a rapid versatile system to verify the efficiency of RNA silencing suppressors that proved to be valuable in enhancing and stabilizing transgene expression in sugarcane.